Memory Enhancing, Anxiolytic and Antidepressant Effects of Achillea biebersteinii (Asteraceae) Essential Oil on Scopolamine-Induced Rats - Akbaba, Emel; Hassan, Salam; Sur, Tarq Mohammed; Bagci, Eyup (Taylor & Francis Ltd, 2018)
The objective of this study was to evaluate the effects of inhaled Achillea biebersteinii Afan. (Asteraceae) essential oil on memory, anxiety and depression in scopolamine-induced amnesic rats. Six groups of adult female Wistar rats (3 months old) were used. These are, control group, Scopolamine - alone-treated group, diazepam alone-treated group, tramadol alone treated group, Sco + A. biebersteinii essential oil 1 % administrated group and Sco + A. biebersteinii essential oil 3 % administrated groups. Memory performances were assessed by Y-maze task and radial-arm maze task. Anxiety and depressive-like behavior were evaluated by elevated plus-maze and forced swimming tasks, respectively. The scopolamine-only administrated group showed impaired spatial memory as evidenced by decrease of the spontaneous alternation percentage in Y-maze test, and increase of the number of working and reference memory errors in the radial arm-maze test. In addition, scopolamine-only administrated group displayed increased anxiety and depressive-like behavior as evidenced by decrease of the exploratory activity, the percentage of the time spent and the number of entries in the open arm within elevated plus-maze test and decrease of swimming time and increase of immobility time within forced swimming test. Achillea biebersteinii essential oil significantly improved memory formation, and reduced anxiety and depression-like behavior in scopolamine-induced rats as compared to scopolamine-alone induced rats. The essential oil of this plant could be a good candidate for complementary therapy against neurological diseases like Alzheimer's disease.
Keywords: Achillea biebersteinii; Alzheimer's disease; scopolamine; memory; anxiety; depression